(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
This article talks about the principles and legal bases of gender equality in Uzbekistan during the years of independence. Based on historical data, the author studied and analyzed specific aspects of the principles and legal bases of gender equality in Uzbekistan during the years of independence on the basis of available scientific literature.